2019
DOI: 10.5935/2595-0118.20190022
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain, anthropometric indexes and range of motion of rural workers

Abstract: BACKGROUND AND OBJECTIVES: This study is necessary considering the expressive number of rural workers that are not assisted by a health professional despite the presence of musculoskeletal changes such as low back pain. Thus, the objective was to check if there is a relationship among low back pain levels, anthropometric measures and range of motion of rural workers. METHODS: A cross-sectional study with rural workers that used the visual analog scale to measure low back pain. The data on body mass index, fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…However, our study found that more nursing technicians were overweight than nurses. It should also be noted that individuals who are classified as overweight and obese showed a higher frequency of low back pain (Nepomuceno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study found that more nursing technicians were overweight than nurses. It should also be noted that individuals who are classified as overweight and obese showed a higher frequency of low back pain (Nepomuceno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain, or lumbago, is a common symptom affecting 60% to 80% of adults worldwide at some point in their life (Nepomuceno et al, 2019). In addition, low back pain is one of the most common work-related musculoskeletal disorders causing absenteeism in the workplace and high medical costs related to treatment, thus being considered a major public health issue Maciel Júnior et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Para isso, o diagnóstico é realizado através do índice de massa corporal(IMC) que é rápido e de reduzido custo, o qual se calcula dividindo o peso em quilogramas pela altura elevada em metros Para se avaliar a circunferência da cintura (CC) é feita uma avaliação através do uso de uma fita inelástica no ponto central entre a última costela e a crista ilíaca ou acima do umbigo, no qual resultados iguais ou maiores a 102 cm para homens e 88 cm para mulheres já apresenta altos riscos à saúde 30 .…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218...unclassified
“…Within the collagen matrix there is an increase in the formation of cross-links, affecting the biomechanics of the discs, possibly resulting in mechanical failures with increased viscosity and reduced tissue elasticity 30 . Therefore, the reduction in fascia elasticity, which may affect the ROM achieved by the joint, would be related to muscle tension and LBP due to the generation of a compression of nerve roots 3,5,9 . Within this context, from a biomechanical approach, stretching exercises could reduce muscle tension on the nerve roots, thus minimizing LBP.…”
Section: Flexibility Stretching and Low Back Painmentioning
confidence: 99%
“…Changes in the connective tissue involving tendons, ligaments, and muscle fasciae caused by factors that directly influence the range of motion (ROM) of a joint (aging, work, immobilization, injuries, metabolism disorders, or nutritional deficiencies) can predispose an individual to LBP 7,8 . In addition, low levels of flexibility of passive muscle structures (tendons, ligaments, and fasciae) may be associated with LBP 9 . In conditions of LBP, the muscles become spasmodic even at rest and the accumulation of metabolites can cause irritation in the nerve endings of the area, generating reflex spasm and increased pain 5,6 .…”
Section: Introductionmentioning
confidence: 99%